Military Responses to the Arab Uprisings and the Future of Civil-Military Relations in the Middle East : Analysis from Egypt, Tunisia, Libya, and Syria - Taylor, William C (New York Palgrave Macmillan, 2014)
This book explains Arab military responses to the social uprisings which began in 2011. Through a comparative case study analysis of Egyptian, Tunisian, Libyan, and Syrian militaries, it explains why militaries fractured, supported the regime in power, or removed their presidents.
Include Tables, Bibliography, Notes and Index
Keywords: Civil-military relations -- Armed Forces--Political activity -- Arab countries